BIOEFFICACY LEVEL OF KAPPAPHYCUS DRIPPINGS AGAINST GOLDEN APPLE SNAIL (Pomacea sp.) - Carmelotes, Henjie A (MATTER: International Journal of Science and Technology, 2018)
The study was conducted to determine whether Kappaphycus Drippings have its molluscicidal property, which will be used to arrest the life of golden apple snail. This was conducted under the vicinity of Southern Philippines Agri-business and Marine and Aquatic School of Technology, Matti, Digos City on February 2014. The study used the Completely Randomized Design with five treatments replicated three times. Treatment 1, treatment 2, treatment 3 and treatment 4 which vary in the amount of Kappaphycus Drippings but they all have the same volume (100ml). Treatment 5 contains the commercial molluscicide that is used to kill golden apple snails. Results of the study showed that the degree of Bioefficacy in terms of treatment 1 to 5 was extremely and very effective. The degree of Bioefficacy of KD concentration implies that pure Kappaphycus Drippings (100ml) without dilution is best in killing the snails. The data also shows that there is a significant difference between the degrees of treatments in killing snails. Furthermore result of the test implies that the second group contains the best treatment in killing the golden apple snail. Moreover, result of the study reveals that there is a significant effect on the use of KD concentration and Niclosamide Ethanolamine Salt against golden apple snail. Future study will determine the chemical properties that enable the agent to arrest golden apple snail.